2022
DOI: 10.3390/nu14132635
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Sweeteners in Breast Milk: A Clinical Investigation with a Kinetic Perspective

Abstract: Artificial sweeteners (ASs) are calorie-free chemical substances used instead of sugar to sweeten foods and drinks. Pregnant women with obesity or diabetes are often recommended to substitute sugary products with ASs to prevent an increase in body weight. However, some recent controversy surrounding ASs relates to concerns about the risk of obesity caused by a variety of metabolic changes, both in the mother and the offspring. This study addressed these concerns and investigated the biodistribution of ASs in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…These authors also described the presence of acesulfame-K and saccharin in 100% and 80% of 15 cord blood samples, with maximum concentrations of 6.5 and 2.7 ng/ml, respectively, while sucralose and steviol glucuronide were not detected (55). A similar study (56) in 49 lactating mothers after the ingestion of acesulfame-K, saccharin, cyclamate, and sucralose, detected their appearance in breast milk at 240-300 min, with maximum concentrations of 936, 81.5 and 2.56 ng/ml Again, these results were independent of the weight and metabolic status of the mothers. The presence of saccharin, acesulfame K, steviol glucuronide and/or sucralose has also been reported in 77% of amniotic fluid (n = 13) samples (55).…”
Section: Nnss In Breast Milk and Amniotic Fluidmentioning
confidence: 70%
“…These authors also described the presence of acesulfame-K and saccharin in 100% and 80% of 15 cord blood samples, with maximum concentrations of 6.5 and 2.7 ng/ml, respectively, while sucralose and steviol glucuronide were not detected (55). A similar study (56) in 49 lactating mothers after the ingestion of acesulfame-K, saccharin, cyclamate, and sucralose, detected their appearance in breast milk at 240-300 min, with maximum concentrations of 936, 81.5 and 2.56 ng/ml Again, these results were independent of the weight and metabolic status of the mothers. The presence of saccharin, acesulfame K, steviol glucuronide and/or sucralose has also been reported in 77% of amniotic fluid (n = 13) samples (55).…”
Section: Nnss In Breast Milk and Amniotic Fluidmentioning
confidence: 70%
“…Most likely, women with a high intake of diet drinks may continue this intake during breastfeeding. We have, in a previous study, shown that ASs ingested by breastfeeding women are transferred to the milk, possibly affecting the nursing infant [21].…”
Section: Potential Mechanisms and Explanationsmentioning
confidence: 95%